Possibility of Benefiting from the Egyptian Experience in Implementing Agricultural Policies to Enhance Food Security in Iraq for the period (2000-2018) - Ali Abdul Husssein, duaa; Nema Ali, Sabah (Journal of Economics and Administrative Sciences, 2024)
Purpose: The research aims to identify the challenges facing the agricultural sector in Egypt in light of the global food crisis and the role of agricultural policies in confronting them considering the available resources and the extent of benefiting from the banking experience in implementing agricultural policies to enhance food security in Iraq.Theoretical framework: The research dealt with the study of agricultural policies and their role in enhancing food security in Iraq by benefiting from the Egyptian experience. The research problem revolves around the fact that the agricultural sector in Egypt faces several challenges, including weak government support for investment in this sector, in contrast to high production costs, the increasing population growth rate, and political and security instability, which led to an increase in the food gap and reliance on abroad to cover local demand for food commodities, especially strategic ones, and the extent of benefiting from the banking experience in implementing agricultural policies to enhance food security in Iraq.Design/methodology/approach: The researcher adopted the deductive method and the descriptive analytical method to study agricultural policies and their role in enhancing food security. The Egyptian experience for the years (2000-2018) was studied and the extent to which it was benefited from in Iraq, especially since that period witnessed a volatile economic situation as a result of the political and economic events that Iraq witnessed.Findings: The analysis of agricultural production relative to local consumption reveals a significant gap, leading to increased reliance on imports to meet domestic demand.Research, Practical & Social implications: The current research contributes to clarifying the role played by agricultural policies in enhancing the level of food security in Iraq by benefiting from the Egyptian experience.Originality/value: The results showed that the number of publications related to banking activities and their role in enhancing market value is increasing, and that the field of economics is the most contributing, as the participating countries provided the largest number of publications.